TINJAUAN KRITIS ATAS TARIKH AL-UMAM WA AL-MULUK KARYA IBN JARIR AL-TABARI - Adnan, Adnan (Al Qalam, 2014)
Tarikh al-Umam wa al-Muluk (history of nations and kings) by Abu Ja'far Muhammad ibn Jarir al-Tabiiri, is by common consent the most important universal history produced in the world of Islam. This monumental work explores the history of the ancient nations, the prophets, the rise of Islam and the history of the Islamic World down to the year 302 A.H./915 AD. His work, chronicled the History of Islam year by year; an attempt to categorize history from creation till the year 302 A.H/915 A.D. By the time he had finished his work, he had gathered all the historical traditions of the Arabs in his voluminous work. The Muslim world was not slow in showing its appreciation, and this work became famous as Islamic Traditional Historiography. However, much to criticize by western scholars (orientalist or lslamicist) sphere in writting style of Thabari work not systematically and interp retatively. In fact, no discovered logical argumen and rational parallel with historical ideas manifesting. The impact of uncommon muslim scholars to become a reference for Islamic historical Studies. A central theme of this paper will be invate of Muslim intellectuals/scholars to be Tarikh Thabari as prominent reference in the Islamic historical studies. Moreover, I will argue that Tarikh al-Umam wa al-muluk by al-Tabari is the most important reference on Islamic history than the other references.